2019
DOI: 10.1155/2019/5390316
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the American Thyroid Association Risk Classification in a Single Center Cohort of Pediatric Patients with Differentiated Thyroid Cancer: A Retrospective Study

Abstract: Introduction. Differentiated thyroid cancer (DTC) is the most common endocrine malignancy in children. Retrospective studies show conflicting results regarding predictors of persistent and recurrent disease after initial therapy. In 2015, the American Thyroid Association (ATA) proposed a clinical classification system to identify pediatric thyroid cancer patients at risk for persistent/recurrent disease. Material and Methods. We retrospectively included all patients in our registry diagnosed with papillary DTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Therefore, follow-up might be less intensive for these patients. In two previous publications, the risk of recurrence of the patients in ER was higher (13-30%) [26,32], and this difference is possibly due to different methods used to classify patients in ER. The probability of achieving ER after initial treatment depended on risk category (from 80% in low-risk to only 15.5% in high-risk patients).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, follow-up might be less intensive for these patients. In two previous publications, the risk of recurrence of the patients in ER was higher (13-30%) [26,32], and this difference is possibly due to different methods used to classify patients in ER. The probability of achieving ER after initial treatment depended on risk category (from 80% in low-risk to only 15.5% in high-risk patients).…”
Section: Discussionmentioning
confidence: 87%
“…Total thyroidectomy and lobectomy remain the main primary surgical interventions for thyroid carcinoma. To date, there has been no large sample randomized controlled clinical trial to compare these two methods, hence their relative efficacy remains controversial and comparative studies have relied mainly on retrospective analyses 2 . This indicates that, although the progress of papillary thyroid carcinoma (PTC) is slow, the ability and tendency to metastasize to lymph nodes and even distant organs are consistent with other malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of the literature with regard to rates of persistent disease in children following treatment for well‐differentiated thyroid cancers. Alwithenani et al reported persistent disease in 27% of children 1 year following treatment for papillary carcinoma thyroid which reduced to 7.3% at 4 years [40]. In another study, 35% had persistent disease two years following treatment which dropped to 21.6% at last follow‐up [41].…”
Section: Discussionmentioning
confidence: 99%